Preference of Three Leaf Yam (Discorea Dumentorum) to Other Types Of Yam Among Farmers in Ibarapa Central Local Government - S.A, Amao; T.A, Adeagbo; B.A, Omotoso; O, Adelayo; O. A, Adebayo; A. A, Oyeleye; J. O, Adisa (International Journal For Research In Agricultural And Food Science, 2017)
The performance of three leaf yam to other yams has greatly influence on the choice of production and the size of land allotted to it. This study was carried out in Ibarapa central local Government Area of Oyo state with a population sample size of eighty (80) respondents. The data were handled with descriptive statistics such as frequency counts, percentages and probit regression analysis. The result of the farmers' socioeconomic characteristics showed that 47.06% of the respondents were male while 47.06% were female. The mean age of the farmers was 59 years while the household size was five - the mean of farming experience was approximately 16 years. The result of probit regression analysis showed that Age, sex, and farmsize are all significant at 1% level while household size was significant at 10%. In conclusion, removing the disparity between the gender and age difference will promote production of three leaf yam in Nigeria as a whole and study area in particular.